A multi-method analysis of distress tolerance in body dysmorphic disorder. (December 2017) - Matheny, Natalie L.; Summers, Berta J.; Macatee, Richard J.; Harvey, Ashleigh M.; Okey, Sarah A.; Cougle, Jesse R.
Highlights: The relationship between DT and BDD symptoms was examined via three studies. Lower DT predicted greater BDD symptoms in community and student samples. Lower tolerance of sadness and anger mood inductions predicted higher BDD symptoms. Tolerance of a fear mood induction was not associated with BDD symptoms. A clinical BDD group reported lower DT than healthy controls. Abstract: Distress tolerance (DT) is a transdiagnostic construct linked to multiple psychiatric disorders. We conducted three studies using different methods to investigate the relationship between DT and body dysmorphic disorder (BDD). Study 1 found a significant relationship between low DT and more severe BDD symptoms in an adult community sample ( N  = 81). In Study 2, we found a similar relationship between lower DT and greater BDD symptoms in a student sample ( N  = 192). Furthermore, we found a unique relationship between greater BDD symptoms and lower self-reported tolerance of anger and sadness mood induction tasks. Greater BDD symptoms were not significantly associated with lower self-reported tolerance of a fear mood induction task. In Study 3, a clinical sample of individuals with BDD ( N  = 40) reported lower DT than a sample of healthy controls ( N  = 36). Findings suggest that low DT is a broad vulnerability factor related to BDD.